Nothing stays unchanged - Kim, Unmi, author; Yust, Dave, 1939-, advisor; Dormer, James T., committee member; Dietemann, David L., committee member; Runyan, William E., committee member (Colorado State University. Libraries, 1989)
The concepts of time and memory have been the dominant influence in my work for a number of years. The two are inextricably linked to the reality in which we live and the manner in which we perceive that reality. It was not my intent to explain or interpret the extent to which these two elements influence the individual's visual perceptions, but rather to accept that influence and utilize its existence as the fundamental concept for the series of paintings completed for the Master’s Thesis Project. The paintings presented here represent my attempts to utilize the concepts of time and memory as an integral element in the development of a visual imagery and in the viewers' perceptions of that imagery. It was my desire to create works which conveyed a sense of history and familiarity designed to provoke the imagination and memory of the viewer; to suggest a mood or atmosphere in an environment which calls on the viewer for individual interpretation.
Keywords: Symbolism in art; Time in art; Memory